Optimasi Model Persediaan Bahan Baku (Raw Material Inventory Model) Pada Industri Kecil Kelompok Pangan Produk Unggulan di Daerah Istimewa Yogyakarta - Makhmudin Ainuri; Adi Djoko Guritno (agriTECH, 1996)
Problems on raw material inventory in food sector small scale industry have been of classical and yet no solution is achived. Specific characteristics found out, such as seasonal, perishasble, and post harvest losses have a significant influence on set up, distribution and warehousing cost. Consequence price fluctuation was observed. Excessive storage capacity means ineffective capital usage, contrarily, too low storage capacity can strike productive line lead to customer unsatisfaction. Optimum model approach on inventory has been taken using constant consideration on several storage and production planning characteristics. Optimum inventory model was developed through direct field observation on individual characteristic of raw materials and its fullfliness characteristic and their link to production planning. QS Software was used to solve EOQ analysis. The object research consist of 4 kinds of small scale industries, that are : emping melinjo (Gnetum g nem on), geplak, tofu (traditional food of soybean material) anda bakery small industries. The result shown that the inventory model of small scale industries Is affected by production rate. Case on emping melinjo industries, the inventory model consist of: (i) inventory model based on lead time greater than zero (ii) in ven tory model based on tolerance of raw material-shortage and (iii) inventory model based on constant production rate (replenishment model). Using the inventory model optimized in this research, raw material distribution controlled by government can be improved. Analysis show that the reorder point and order interval can be reduced (in cased of sugar and flour raw material). Fluctuation pricing of raw material provoque augmentation of total cost and order interval (in case of coconut raw material).